Ichthyosis Follicularis, Atrichia, and Photophobia (IFAP) Syndrome, Type 2: Clinical Case - Eduard T. Ambarchyan; Anastasiya D. Kuzminova; Totuy K. Eldarova; Vladislav V. Ivanchikov; Nataliya V. Zhurkova; Nato D. Vashakmadze (Вопросы современной педиатрии)
Background. Ichthyosis follicularis with atrichia and photophobia (IFAP syndrome), type 2 is a rare hereditary disease from the group of syndromic forms of ichthyosis. It is clinically characterized by triad of non-inflammatory follicular ichthyosis, total or subtotal alopecia at birth or shortly after, and photophobia of different severity. There is no etiotropic therapy for IFAP syndrome, while symptomatic treatment (emollients, keratolytics, retinoids) is aimed on stabilizing the patient’s condition and maintaining the optimal quality of life. About 60 cases of IFAP syndrome have been described worldwide by 2023, and none in Russia.Clinical case description. The girl, 2 years 3 months old, had signs of xeroderma, follicular hyperkeratosis, photophobia with lacrimation, and alopecia. The diagnosis of “ichthyosis follicularis with atrichia and photophobia (IFAP syndrome), type 2, autosomal dominant” was established according to anamnesis, clinical signs, and results of whole-exome sequencing, followed by validation of the identified nucleotide variant chr17:17720597G>A, p.1669C>T (p.Arg557Cys NM_001005291.2) in exon 9 of the SREBF1 gene via direct automatic sequencing in the patient and both parents (not revealed in her parents).Conclusion. Molecular genetic testing is crucial to establish IFAP syndrome as clinical signs of the disease are similar to other dermatoses. However, physicians need to have clinical suspicion when identifying cases of follicular ichthyosis in combination with alopecia and photophobia at or shortly after birth to timely diagnose IFAP syndrome and thus prevent any treatment delays.